Strategi Shadow Teacher dalam Proses Pembelajaran pada Anak Berkebutuhan Khusus (Tunawicara) di Sekolah Alam Mahira Kota Bengkulu - Andani, Fidhia; Windhana, Allysyah Putri; Putri, Yespa Gustia; Mubarakah, Wija; Usiwardani, Choldia Heldiyanti (JPT : Jurnal Pendidikan Tematik, 2023)
This study aims to determine the shadow teacher strategy in the learning process of children with speech impairments at the Mahira Nature School in Bengkulu City. This research is important to conduct in order to understand the learning strategies for children with speech impairments. This research method uses a qualitative method of descriptive subjects conducted with teachers. This study used questions for direct observation interviews with teachers. The results of the study indicate that the teacher's strategy in learning children with speech impairments uses unique media and other teaching aids so that they can be easily understood by the children with speech impairments.